Development of Contextual-Based Mathematics Learning Tools on the Subject of Comparison - Risma Ismail; Andi Ika Prasasti Abrar; Fitriani Nur; Suharti Suharti; Andi Halimah (Universitas Jambi, 2021)
The learning process cannot be separated from the use of learning tools, the entire learning process has been planned in these learning tools. This study aims to produce a contextual-based mathematics learning tool on the subject of comparison of class VII SMPN 27 Makassar which is valid, practical and effective. The type of research used is research and development (R&D) with reference to the 4-D Thiagarajan model, namely: (1) the define stage, (2) the design stage, (3) the develop stage, and (4) the disseminate stage. The instruments used were validation sheets, student response questionnaires, observation sheets for device implementation, and learning outcomes tests. Based on the results of the validation of the experts, the products developed and the instruments used for each aspect were in the "valid" to "very valid" category on average. In the field trial, it was found that: (1) the instrument used to measure the practicality found that the device developed was carried out well, the average value of all aspects of the observation was carried out and the response questionnaire analysis was in the "positive" category (2) the instrument for measuring the effectiveness The data obtained from the test of learning outcomes with an average score of students reaching 83.3%, student activity was as expected, and observations of learning management were in the high category. So that this study produces a contextual-based mathematics learning tool product on the subject of comparison of class VII SMPN 27 Makassar which is valid, practical and effective.